Energy saving formation control of multi-robot systems - Peck, Weixiang (2016)
In modern world, most products are make to be as compact as possible but did not reduce the usability of the products. One such product was the robot. It has been notice that some of the robots are compact in size and yet able to complete the objective they have. As they are compact in size, most of them are battery operated and it is definitely a must for them to complete the task before the power runs out. This project will compare the energy efficiency of multi robot system with the use of poweranalyser. It compares two different control methods mainly the Model Predictive Control (MPC) and Close Loop Control with the use of the same controller for each individual method. The test was done by allowing the robot to reach its target location with the help of each control method. The robot was to link with the computer via Bluetooth as the computer works as the central processing unit. The data was being processed by the computer before data was transferred to the robot through Bluetooth. To allow a better comparison, it is recommended to use a different robot for the same test. If the result tallies with the result of this project, we will have a better understanding. Also, we can have a different task to see the energy consumption of the robot and compare the result with this experiment. In conclusion, MPC have a higher advantage as compared to the Close Loop Control as it has a lower energy consumption as compared to the Close Loop Control.